Use of Donor with Wolff-Parkinson-White Syndrome in Heart Transplantation: Report of Two Cases and Review of Literature - Antonio Groppo Solf, Noedir; Honorato, Ronaldo; Fiorelli, Alfredo; Bacal, Fenando; Jatene, Fabio (Brazilian Journal of Transplantation, 2022)
Donor shortage is a major limitation of heart transplantation. The use of high risk or marginal donors, donors with minor or correctable heart diseases are alternatives to face this problem. When identified in the evaluation, donors with Wolff-Parkinson-White syndrome (WPWS) are usually discarded for cardiac transplantation. In the literature, there are eight articles reportingsingle case of transplantation with donor with this syndrome. In this series, the management of recipient varied: clinical treatment, intraoperative donor heart anomalous band ablation and postoperative ablation. Results were good in all the eight cases. In the present article, we report two cases of cardiac transplantation with donors with WPWS, one treated clinically and the other one submitted to postoperative ablation. Based in the present experience and limited to eight reported cases, it seems that this type of donor heart can besuccessfully transplanted. It is controversial the management strategy for these patients. Careful evaluation of heart donor should be done regarding the presence of WPWS.